Respuesta :
The equivalent expression is option (B) x^2/3 is the correct answer.
What is an equivalent expression?
An equivalent expression is an expression that has the same value but does not look the same. When you simplify an expression, you're basically trying to write it in the simplest way possible.
For the given situation,
The expression is [tex](x^{\frac{4}{3} }x^{\frac{2}{3} } )^{\frac{1}{3} }[/tex]
The equivalent expression can be obtained as
⇒ [tex](x^{\frac{4}{3}+\frac{2}{3} } )^{\frac{1}{3} }[/tex] [ ∵ [tex]x^{a} x^{b}=x^{a+b}[/tex]]
⇒ [tex](x^{\frac{6}{3}} )^{\frac{1}{3} }[/tex]
⇒ [tex]x^{(\frac{6}{3}) (\frac{1}{3}) }[/tex] [∵ [tex]x^{(a)(b)}=x^{ab}[/tex]]
⇒ [tex]x^{\frac{6}{9} }[/tex]
⇒ [tex]x^{\frac{2}{3} }[/tex]
Hence we can conclude that the equivalent expression is option (B) x^2/3 is the correct answer.
Learn more about equivalent expression here
https://brainly.com/question/11326971
#SPJ2